Forage performance and detection of marker trait associations with potential for Napier grass (Cenchrus purpureus) improvement - Habte, Ermias; Muktar, Meki S.; Abdena, Asebe; Hanson, Jean; Sartie, Alieu; Negawo, Alemayehu T.; Machado, J.C.; Silva Ledo, F.J. da; Jones, Christopher S. (MDPI, 2020)
The evaluation of forage crops for adaptability and performance across production systems and environments is one of the main strategies used to improve forage production. To enhance the genetic resource base and identify traits responsible for increased feed potential of Napier grass, forty-five genotypes from Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), Brazil, were evaluated for forage biomass yield and feed nutritional quality in a replicated trial under wet and dry season conditions in Ethiopia. The results revealed significant variation in forage yield and feed nutritional qualities among the genotypes and between the wet and dry seasons. Feed fiber components were lower in the dry season, while crude protein, in vitro organic matter digestibility, and metabolizable energy were higher. Based on the cumulative biomass and metabolizable energy yield, top performing genotypes were identified that are candidates for future forage improvement studies. Furthermore, the marker-trait association study identified diagnostic single nucleotide polymorphisms (SNP) and SilicoDArT markers and potential candidate genes that could differentiate high biomass yielding and high metabolizable energy genotypes in the collection.